Controlled Substance Management in Chronic Pain A Balanced Approach - Staats, Peter S.; Silverman, Sanford M. (Springer International Publishing : Imprint: Springer, 2016)
This comprehensive guide covers prescribing controlled substances for patients with acute or chronic pain and provides a balanced discussion on appropriate treatment, addiction, safety and complications. Chapters feature evidence-based strategies and clinical modalities that address diagnostic challenges, treatment guidance, alternatives to opioid management and the significant legal risks within the current regulatory environment. Authored by leaders in pain medicine, physicians and appropriate health care professionals will find Controlled Substance Management in Chronic Pain to be an indispensable resource. .